Scrutiny of power grids by penetrating PV energy in wind farms: a case study of the wind corridor of Jhampir, Pakistan - Soomar, Arsalan Muhammad; Guanghua, Lyu; Shaikh, Shoaib; Shah, Syed Hadi Hussain; Musznicki, Piotr (Frontiers in Energy Research, 2023)
This study examines the problems caused by intermittent renewable energy sources, especially wind farms, and suggests a different solar energy penetration strategy to improve their loading capacity. The study uses real-time data from a wind farm in Jhampir, Pakistan, to analyse and assess various aspects of grid stations connected to wind farms. Linking the results to concrete factual facts is validated with the help of the Electrical Transient Analyzer Program (ETAP). The article focuses on creating a model for a grid-connected to a wind farm and the simulation of outcomes following capacity expansion with the installation of an autotransformer. The original capacity of the wind farm was 750MW, which was increased to 1250MW, i.e., 1.66 times the actual capability. Furthermore, this capacity was further enhanced to 1540 MW, which becomes 1.23 times the previous capacity by penetration of a PV power plant.